THE TRANSLATION OF PREPOSITION “OF” FROM ENGLISH INTO INDONESIAN - Diana, Rose; Said, Mashadi (Universitas Gunadarma, 2017)
This is a descriptive analysis study which focuses on the translation of preposition “of” from English into Indonesia with using novel Potter and the Chamber of Secrets and its translation as its objects of the research. In this research, the researcher wants to find out; 1.) What are Indonesian translations of preposition “of” in the novel Harry Potter, 2.) What are the plausible reasons of translating preposition “of” into Indonesians according to translation theories (principle and strategy of translation). So, the aims of this research are; 1.) to find out Indonesian translation of preposition “of” in the novel Harry Potter and the chamber “Of” Secrets, 2.) to find out the plausible reasons of translating preposition “Of” into Indonesians according to translation theories (principle and strategy of translation). The result of this research shows that there are 23 ways in translating preposition “of” from English into Indonesian and there are 3 categories of plausible reasons that could be given, namely a.) not translated, b.) translated into Indonesian Preposition, c.) translated into Indonesian other parts of speech. So, this research provides better knowledge in translating preposition “of” into Indonesian by not using the same translation for preposition “of” in every context since each context may have different translation for preposition “of” depends from its meaning and function, and that by using the same translation of preposition “of” in every context without considering its meaning and function will lead the translation into a mistake. Keywords: Descriptive analysis, preposition, translation strategies, translation principles.